DFT/TD-DFT study of novel triphenylamine-based dyes with azo moieties and π-spacer variations for enhanced dye-sensitized solar cell performance - Jubaer Ahmod Shakil; Shassatha Paul Saikat; Niloy Bhattacharjee; Md. Rithoan Hossain; Mahafuz Hossen; Jahidul Islam; Mayeen Uddin Khandaker; Jamal Uddin; Faisal Islam Chowdhury (Chemical Physics Impact)
This study involves a computational analysis of new D-π-A dyes obtained from triphenylamine (TPA), which contain various azo-dye components. The structural, molecular, electrical, and optical properties of these dyes were computed using Density Functional Theory (DFT) and Time-Dependent DFT, utilizing the B3LYP/6–31 G model. Our research specifically aimed to investigate the effects of incorporating different azo dye constituents in the para position of two phenyl groups of TPA. The results indicate that these alterations lead to notably broadened and red-shifted absorption spectra, as well as improved optoelectronic properties that are subject to additional tuning through the manipulation of the π-spacer. The excitation energies and HOMO-LUMO energy levels that have been estimated indicate the presence of effective electron injection and dye regeneration mechanisms. The results concerning the nonlinear optical (NLO) properties suggest that these dyes are likely to demonstrate superior performance in NLO applications. The factors encompassed in this study consist of light-harvesting efficiency (LHE), open-circuit photovoltage (VOC), electron injection driving force (ΔGinj), dye regeneration driving force (ΔGreg), excited state lifetime (τ) and reorganization energy (λtotal), which has a strong correlation with the electrical current density in a short-circuit (JSC) and DSSC's overall effectiveness. This scientific attempt contributes to the systematic advancement of efficient dyes, demonstrating the possibility for enhanced efficiency in DSSCs. Further validation of computational forecasts and advancement of renewable energy technology necessitate future experimental synthesis and testing.